Penerapan Pembelajaran Holistik Berbasis Karakter Pada Sistem Pembelajaran Di Paud Samudera Kasih Kota Bengkulu - Putri, Suci Nurhaliza (Jurnal Pendidikan Rafflesia, 2024)
This study aims to describe the application of character-based holistic learning in the learning system at PAUD Samudera Kasih in Bengkulu City. The type of research used in this research is descriptive qualitative research. The data collection methods used were interviews, observation and documentation. The data sources are PAUD teachers and the principal of PAUD Samudera Kasih in Bengkulu City and documentation in the form of character-based holistic learning tools used in PAUD. The data analysis techniques used are data reduction, recording the results of interviews with teachers, school principals and parents, taking notes, coding the data according to the information provided by the informant, displaying data explaining the results of interviews with teachers and school principals, and verifying the data, rethinking the results. interviews, reviewing field notes, rethinking observation data and findings in the field, in order to draw conclusions from the results of the research that has been carried out. The results of this research describe the application of character-based holistic learning in the learning system carried out or implemented at PAUD Samudera Kasih in Bengkulu City.